BEBBINGTON'S APPROACH TO EVANGELICAL CHRISTIANITY AS A PIONEERING EFFORT IN LIVED RELIGION. - Porterfield, Amanda (Fides et historia, 2015)
The article considers British historian David W. Bebbington's approach to evangelical Christianity as a pioneering effort in lived religion. It explores the definition of evangelicalism based on Bebbington's book "Evangelicalism in Modern Britain." It examines U.S. religious history to explain the link between Bebbington's work and lived religion. The article also suggests that the affective aspect of American evangelicalism does not contradict Bebbington's quadrilateral thesis.